PENGARUH PENGGUNAAN ROOLER ROCKER ARM TERHADAP DAYA PADA SEPEDA MOTOR SOHC 200 CC BERDASARKAN PARAMETER DYNOTES - Mohamad, Mohamad Rafli; Kurniawan, Ahmad; A. Daniel, Mohammad Ikbal Rizki (JoVI:JOURNAL of VOCATIONAL INSTRUCTION, 2024)
This research aims to find out: 1) To find out how powerful a 200 CC SOHC motorbike is using a standard rocker arm. 2) To find out what the power of a SOHC 200 CC motorbike is with a rocker arm that uses a roller. 3) To find out whether there is an effect of using a rocker arm that uses a roller on the power of a SOHC 200 motorbike. The data collection technique used in this research is by carrying out testing a motorbike using a dynotest tool: 1) Testing is carried out starting with a motorbike using a standard rocker arm and then testing on the same motorbike by installing a rocker arm that uses a roller. 2) This was done 3 times for each rocker arm to get accurate results. The research results showed that: 1) At 7000 rpm the engine power produced when using a standard rocker arm was 13.9 hp. Meanwhile, when using a roller rocker arm, the resulting engine power is 16.2 hp. 2) At 7250 rpm the engine power produced when using a standard rocker arm is 15.7 hp. Meanwhile, when using a roller rocker arm, the resulting engine power is 16.8 hp. 3) At 7500 rpm the engine power produced when using a standard rocker arm is 16.6 hp. Meanwhile, when using a roller rocker arm, the resulting engine power is 17.0 hp. 4) At 7750 rpm the engine power produced when using standard rocker arms is 16.7 hp. Meanwhile, when using a roller rocker arm, the resulting engine power is 16.9 hp.